A network model links wood anatomy to xylem tissue hydraulic behaviour and vulnerability to cavitation - Mrad, Assaad; Domec, Jean‐Christophe; Huang, Cheng‐Wei; Lens, Frederic; Katul, Gabriel (Plant, cell and environment, 2018)
Plant xylem response to drought is routinely represented by a vulnerability curve (VC). Despite the significance of VCs, the connection between anatomy and tissue‐level hydraulic response to drought remains a subject of inquiry. We present a numerical model of water flow in flowering plant xylem that combines current knowledge on diffuse‐porous anatomy and embolism spread to explore this connection. The model produces xylem networks and uses different parameterizations of intervessel connection vulnerability to embolism spread: the Young–Laplace equation and pit membrane stretching. Its purpose is upscaling processes occurring on the microscopic length scales, such as embolism propagation through pit membranes, to obtain tissue‐scale hydraulics. The terminal branch VC of Acer glabrum was successfully reproduced relying only on real observations of xylem tissue anatomy. A sensitivity analysis shows that hydraulic performance and VC shape and location along the water tension axis are heavily dependent on anatomy. The main result is that the linkage between pit‐scale and vessel‐scale anatomical characters, along with xylem network topology, affects VCs significantly. This work underscores the importance of stepping up research related to the three‐dimensional network structure of xylem tissues. The proposed model's versatility makes it an important tool to explore similar future questions. This work introduces a new open source numerical model of plant xylem. The subject of inquiry is the link between wood anatomy and plant water use, especially vulnerability to embolism under drought. The model successfully reproduces empirical vulnerability curves of Acer terminal branches. The results of this study underscore the importance of stepping up research on the effects of xylem network topology on whole‐plant hydraulics.